Marketing for hospitality and tourism - Kotler, Philip (Boston ; London Pearson, 2010)
Prepares students for taking an active part in the business world by providing them with a strategy for learning and for practice. The new edition has an even stronger emphasis on strategy planning and marketing decision process. There are over 40 mew cases drawn from the entire Asia-Pacific region.
Keywords: (MASB-1902) Marketing for hospitality and tourism; (MASB-2901) Tourism and Hospitality Sales and Promotion